# Calculate $1+(1+2)+(1+2+3)+\cdots+(1+2+3+\cdots+n)$

How can I calculate $1+(1+2)+(1+2+3)+\cdots+(1+2+3+\cdots+n)$? I know that $1+2+\cdots+n=\dfrac{n+1}{2}\dot\ n$. But what should I do next?

• – lhf
Commented Oct 19, 2014 at 15:03
• A geometric proof of sum of squares. Commented Oct 19, 2014 at 15:16

Sorry for the horrible resolution. In any case: That's Pascal's triangle. The blue is the triangular numbers. The red is the sum of the blue (can you see why?)

Now you can use the formula for the elements of Pascal's triangle: The $n$th row and $r$th column is $\dbinom nr$. (You start counting the rows and columns from 0. The rows can be counted from the left or the right, doesn't matter.)

The answer is $\dbinom{n+2}3=\dfrac{n(n+1)(n+2)}{3!}$.

• Can you see why the blue are the triangular numbers, by the way? Commented Oct 19, 2014 at 15:21
• +1 for not just offering the combinatorial answer (which is much cleaner than going through any sum-of-squares formula) but doing a great job of explaining why it's true. This is IMHO the best answer by far here. Commented Oct 19, 2014 at 16:24
• brilliant!${{{}}}$ Commented Oct 19, 2014 at 16:25

Hint: use also that $$1^2 + 2^2 + \dots + n^2 = \frac{n(n+1)(2n+1)}6$$

$$1 + (1+2) + \dots + (1 +2+\dots +n) = \frac{1(1+1)}2 + \frac{2(2+1)}2 + \dots + \frac{n(n+1)}2 \\=\frac 12 \left[ (1^2 + 1) + (2^2 + 2 ) + \dots + (n^2 + n) \right] \\=\frac 12 \left[ (1^2 + 2^2 + \dots + n^2) + (1 + 2 + \dots + n) \right]$$

\begin{align} &1+(1+2)+(1+2+3)+\cdots+(1+2+3+\cdots+n)\\ &=n\cdot 1+(n-2)\cdot 2+(n-3)\cdot 3+\cdots +1\cdot n\\ &=\sum_{r=1}^n(n+1-r)r\\ &=\sum_{r=1}^n {n+1-r\choose 1}{r\choose 1}\\ &={n+2\choose 1+2}\\ &={n+2\choose 3}\\ &=\frac16 n(n+1)(n+2) \end{align}

• This seems to be wrong as the last expression is the sum of the first $\;n\;$ squared natural numbers, which is not what we have. Commented Oct 19, 2014 at 16:16
• Not really... the sum of the first $n$ squared natural numbers is $\frac16 n(n+1)(2n+1)$ Commented Oct 19, 2014 at 16:18
• Oh, I see now the second parentheses more carefully. Thanks. +1 Commented Oct 19, 2014 at 16:24

$$\sum_{k=1}^n(1+\ldots+k)=\sum_{k=1}^n\frac{k(k+1)}2=\frac12\left(\sum_{k=1}^nk^2+\sum_{k=1}^nk\right)$$

and now

$$\sum_{k=1}^nk^2=\frac{n(n+1)(2n+1)}6$$

HINT :

It is the summation of $\sum \frac {n(n+1)}2$ from 1 to n

which is equal to $\sum (\frac {n^2}2 + \frac n2)$ from 1 to n

I thought about this problem differently than others so far. The problem is asking you to essentially sum up a bunch of sums. So by observation, it appears that $1$ appears $n$ times, $2$ appears $n-1$ times, $3, n-2$ times and so on, with only $1$ $n$ term. So instead, let's add up a sum from $1$ to $n$ which does this. It should be of the form $\sum_{i=1}^{n} n(n+1)=\sum_{i=1}^{n}n^2+n.$ Since sums are linear, decompose this into two sums, and apply the formulas you know for the sum of the squares and the sum of the integers.

Sums we know:
$\sum^n_{i=1} i = 1+2+\cdots+n=\frac{n^2+n}{2}$
$\sum^n_{i=1} i^2 = 1^2 + 2^2 + \dots + n^2 = \frac{n(n+1)(2n+1)}6$

Your sum is $$(1+2+3+ \cdots + n) + (1 + 2 + \cdots + (n-1)) + (1 + 2 + \cdots + (n-2)) + \cdots + (1)$$ $$= \sum^n_{k=1} \sum^k_{i=1} i$$ $$= \sum^n_{k=1} \frac{k^2+k}{2} = \frac 12 (\sum^n_{k=1} k^2 + \sum^n_{k=1} k)$$

NOTE: You can reorder the terms if the are a finite number of them. So if you're going to be taking a limit as $n \to \infty$ don't do it this way.

The n-th partial sum of the triangular numbers as listed in http://oeis.org/A000292 .